Book Review of Stuart Elden – Terror and Territory: the Spatial Extent of Sovereignty (Geografares, 2014)
The text consists of one review of the book Terror and territory: the spatial extent of sovereignty (2009) English geographer Stuart Elden. The work provides an approach of territory as the spatial extent of political sovereignty, which conceives importance to the notion of terror as a fundamental quality of the territory as a form punitive of control executed within the recognized boundaries, through use the monopoly of legitimate violence that state power has. However, the territorial sovereignty that evokes modern state, Elden argues, has become contingent after the terrorist attacks of September 11 (2001), when the USA unleashed a policy of “war on terror”, unilaterally applying the law of international intervention.
Keywords: Terror; Territory; Sovereignty